2015
DOI: 10.1007/s12161-014-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Three Trace Organophosphorus Pesticide Residues in Vegetables Using Molecularly Imprinted Solid-Phase Extraction Coupled with High-Performance Liquid Chromatography

Abstract: In this study, a molecularly imprinted polymer that can selectively recognize dimethoate, isocarbophos, and methyl parathion was synthesized. Using this compound as sorbent, a new method for simultaneous determination of the three organophosphorus pesticides by molecularly imprinted solid-phase extraction coupled with high-performance liquid chromatography was established. The factors affecting the preconcentration and sensitivity were studied in detail. Under optimal conditions, the limits of detection of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…As mentioned by some authors, the selection of the monomer(s) and the template/monomer(s) ratio can be carried out by studying the changes in UV spectra of the template when adding increasing concentration of the monomer in the solvent selected for the synthesis [67,69,77]. Other spectroscopic methods were used such as NMR to highlight the presence of hydrogen bonds between the template and MAA [39,67,69,72,73] and FT-IR to highlight the interactions between OPP and OH-group of MAA [39,46,55,61,70,76,80,91,97,98,102]. This method was also used to control the template removal by comparing MIP spectrum before and after its washing [64,93,99], this control being most of the time ensured by analyzing the template amount in the washing solution by UV detection or by chromatographic analysis.…”
Section: Synthesis Of Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by some authors, the selection of the monomer(s) and the template/monomer(s) ratio can be carried out by studying the changes in UV spectra of the template when adding increasing concentration of the monomer in the solvent selected for the synthesis [67,69,77]. Other spectroscopic methods were used such as NMR to highlight the presence of hydrogen bonds between the template and MAA [39,67,69,72,73] and FT-IR to highlight the interactions between OPP and OH-group of MAA [39,46,55,61,70,76,80,91,97,98,102]. This method was also used to control the template removal by comparing MIP spectrum before and after its washing [64,93,99], this control being most of the time ensured by analyzing the template amount in the washing solution by UV detection or by chromatographic analysis.…”
Section: Synthesis Of Mipsmentioning
confidence: 99%
“…three molecules that comprise an aromatic ring with one or two linked nitrogen atoms [97]. Some authors reported the ability of the MIP to extract up to six OPPs with high recovery rates but the NIP was not used in parallel to the MIP when optimizing the SPE procedure [42,50,61,68,76,80]. In these conditions, the retention was certainly favored by the solvent selected as percolating medium but the real selectivity, believed to being brought by the cavities of the MIP, was not really proven.…”
Section: -1-mip-spe Of Oppsmentioning
confidence: 99%
“…The development of MIPs for the extraction of OPs has been largely reported these last years. MIPs were prepared as particles to be used in cartridges between two frits as SPE sorbent [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] or as dispersive sorbent for dSPE [27][28][29][30][31] and for matrix solid-phase dispersion (MSPD) [32][33][34] or as a thin film in solid-phase microextraction (SPME) [35][36][37] or in stir bar sorption extraction (SBSE) [38]. They were applied to the selective extraction of OPs from vegetable extracts (cucumber, lettuce, apple, pear…) and environmental samples such as waters and soil extracts.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison between MIP and NIP achieved in spiked pure media allows to put in evidence the presence of cavities in the MIP and is also useful to optimize the extraction procedure that must give rise to high extraction recovery on the MIP and low one on the NIP [8]. Except for one reported work [21], the conditions of extraction finalized in pure media were applied to real samples [11,[17][18][19][20][22][23][24][25][26][27]38] without a control of the selectivity by using the NIP or without reoptimization of the extraction conditions to circumvent matrix effects as already reported [8]. These matrix effects were well illustrated by Sanagi et al who reported recoveries obtained in pure media and in real samples after applying the same extraction procedure on MIP and on NIP [21].…”
Section: Introductionmentioning
confidence: 99%
“…До традиційних методів визначення афлатоксинів відносять тонкошарову хроматографію [6], високоефективну рідинну хроматографію (ВЕРХ) [7], різні поєднання рідинної хроматографії з мас-спектрометрією [8] та імуноферментний аналіз [9]. Для визначення фосфороорганічних пестицидів використовують хроматографічні методи [10][11][12][13], включаючи ВЕРХ [14,15] та газову хроматографію [16]. Методи, що дозволяють визначати важкі метали (наприклад, кадмій, ртуть, свинець, миш'як, олово, селен, сурму, мідь, нікель, хром, телур, талій), включають атомно-абсорбційну або емісійну спектроскопію, рентгенівську флуоресцентну спектрометрію, хроматографічні або електрохімічні методи аналізу [17][18][19].…”
Section: афлатоксин G2unclassified